Students’ Challenges in Academic Writing for Cross-Border Communication and Translanguaging Pedagogy to Promote Glocalization - Katharina Rustipa; Endang Yuliani Rahayu; Teguh Kasprabowo; Yulistiyanti Yulistiyanti; Monica Evelyne Davantya Setiaji (Vision: Journal for Language and Foreign Language Learning, 2025)
For academicians, publishing in international journals means engaging in a border-crossing activity, as they disseminate their research findings globally. People from various countries with different cultures and norms read research papers. However, academic writing is problematic for non-native English-speaking students (NNES), as prospective academics. This review paper aims to identify the challenges that NNES face in writing research article introductions (RAIs), including rhetorical structures, tense choice, tense shift, clausal and phrasal complexity, and the benefits of using translanguaging techniques in academic writing classes. Thematic analysis was employed in this library study. The research procedure involves selecting relevant research articles on the topic, reading each article, taking notes on the key findings, integrating and discussing the findings from the reviewed articles, and designing translanguaging techniques to teach academic writing to NNES. The article review reveals that NNES face challenges in writing complete rhetorical structures, particularly in tense choice and tense shift, because in academic writing, tense usage is not only governed by time but also by the rhetorical concept. It also reveals that translanguaging techniques facilitate the students’ awareness of the native language and target language academic writing rules and conventions. Translanguaging techniques enhance students’ analysis skills, critical reading, and critical thinking.